Édition critique numérique avec le logiciel Ekdosis pour LuaLaTeX. L’exemple des fragments latins d’atellanes - Estelle Debouy (Humanités Numériques)
The benefits of digital editions do not need to be demonstrated: surely, the edition text can be enriched with comments, multiple translations, grammatical annotations, metrics, and so forth. Furthermore, the encoding of the text and the associated apparatus in XML-TEI turns the edition into a database that can be consulted by the reader according to various needs.The TEI provides accurate standardised elements for the description of handwritten sources. However, TEI-encoded apparatuses are not so much meant to be interpreted by humans as processed by machines. In this respect, the Ekdosis LuaLaTeX package developed by Robert Alessi is a precious tool for philologists undertaking to make a critical edition of an ancient text, for it allows them to type in LaTeX every item of the edition (variants, sources, translation, commentary) while requesting at the same time PDF and XML-TEI ouput files, the former to be read and the latter to be searched. As a result, Ekdosis appears as a tool that combines two needs: that of producing a printed edition in compliance with philological traditions and that of providing what Donald J. Mastronarde and Richard J. Tarrant have called “actionable texts for use in digital research”.The purpose of this article is to expose, based on a commented example taken from my edition of the atellanae, the method I followed to write with Ekdosis the constituent elements of a digital critical edition.